PENGARUH PENGETAHUAN TENTANG LINGKUNGAN HIDUP, KEARIFAN LOKAL, LOCUS OF CONTROL, DAN MOTIVASI BERTANI TERHADAP PERILAKU LINGKUNGAN YANG BERTANGGUNG JAWAB PETANI DI KABUPATEN SOPPENG - Mulyadi Mulyadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2015)
Responsible environmental behavior is assumed to be significantly affected bay one’s knowledge of the environment, the local wisdom, locus of control motivation farming. The study reported here aimed to examine how the four independent variables actually affected the level of farmers’ responsible behavior towards environment. The causal and multidimensional social study was conducted in the Soppeng Regency of South Sulawesi from July 2009 to October 2009, trough a survey to the paddy farmers in the Liliriaja District. A sample of 120 farmers was made up 30 randomly selected farmers from each of the four purposefully selected sub districts in Liliriaja: Appanang, Galung, Rompegading and Jampu. The data of each variable were collected separately with a questionnaire. A path technique, which was preceded by normality and variance homogeneity tests, was employed to analyze the data descriptively and inferentially. The results proved that the farmers’ farming motivation and their responsible environmental behavior, respectively, was directly affected by their knowledge of the environment, the local wisdom, and the locus of control. The three independent variables also indirectly affected the farmers’ responsible environmental behavior through their motivation in farming. These findings suggest that the variables of environmental knowledge, local wisdom, locus of control and the farmers’ motivation in farming are important determinants of their responsible environmental behavior. Variation in the farmers’ responsible environmental behavior may therefore be minimized by improved knowledge of the environment, local wisdom, locus of control and farming motivation.